THE EFFECT OF QUICK WRITE STRATEGY ON STUDENTS’ ABILITY IN WRITING EXPOSITION TEXT - Gazela,, Aldera L.; Suhami (GoAcademica CRP, 2024)
Good writing skills are very important for students in facing academic challenges. However, students often have difficulty in writing exposition texts well. This study examines the effect of a speed writing strategy on students' writing ability in the context of analytical exposition texts. The type of research is experimental. The population in this study were all students of SMA Negeri 3 Sungai Penuh, and the samples were the control class (XI IPS 2) and the experimental class (XI IPA 1) determined by random sampling technique. data was collected by a test on exposition text writing skills. The results showed that the control class did not show significant improvement in their writing skills, as the average scores on both tests fell into the